Analisis Estimasi Pembuatan Perangkat Lunak Dengan Menggunakan Metode Constructive Cost Model (COCOMO) - Ivan, Daniel; Rusdi, Zyad; Tumbelaka, Bobby (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
The COnstructive COst MOdel, COCOMO, was developed to estimate the effort and cost to complete a software project. All business enterprises involved in developing software must know their costs to maintain their long-term viability. COCOMO measures the size of the project is lines of code. When the size of the project is measured in function points, COCOMO uses a function points to lines of code converter. However, function points is the better metric of project size. We present a new model which uses function points as a direct input into the model. We show that the software project data can be analyzed on a programming language basis. We claim that our proposed model is superior because it eliminates the errors introduced by arbitrary function point indices and replaces them with constants that are scientifically verifiable. Key words COCOMO, Constructive Cost Model, Estimasi Usaha